2009
DOI: 10.1124/dmd.109.028290
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CYP3A by Erythromycin: In Vitro-In Vivo Correlation in Rats

Abstract: ABSTRACT:The prediction of in vivo drug-drug interactions from in vitro enzyme inhibition parameters remains challenging, particularly when time-dependent inhibition occurs. This study was designed to examine the accuracy of in vitro-derived parameters for the prediction of inhibition of CYP3A by erythromycin (ERY). Chronically cannulated rats were used to estimate the reduction in in vivo and in vitro intrinsic clearance (CL int ) of midazolam (MDZ) after single and multiple doses of ERY; in vitro recovery of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…To rule out any other possible pharmacokinetic interference by antibiotics, such as effects on cytochrome P450 enzymes or drug efflux pumps, lovastatin was administered 3 days after antibiotic treatment, when the antibiotics should have been eliminated from the body. Although erythromycin, which was included in COE, is considered as a time-dependent inactivator of CYP3A, it has been found that a single dose of erythromycin does not form a metabolic intermediate complex, i.e., it does not inactivate CYP3A4 (Zhang et al, 2010). Thus, the potential inhibition of the hepatic metabolism of lovastatin by erythromycin would be negligible.…”
Section: Resultsmentioning
confidence: 99%
“…To rule out any other possible pharmacokinetic interference by antibiotics, such as effects on cytochrome P450 enzymes or drug efflux pumps, lovastatin was administered 3 days after antibiotic treatment, when the antibiotics should have been eliminated from the body. Although erythromycin, which was included in COE, is considered as a time-dependent inactivator of CYP3A, it has been found that a single dose of erythromycin does not form a metabolic intermediate complex, i.e., it does not inactivate CYP3A4 (Zhang et al, 2010). Thus, the potential inhibition of the hepatic metabolism of lovastatin by erythromycin would be negligible.…”
Section: Resultsmentioning
confidence: 99%
“…1). A significant number of DDIs are believed to arise from the formation of MI complexes by alkyl amine-containing drugs (Backman et al, 1994;Mayhew et al, 2000;Hall et al, 2003;Zhang et al, 2010). Considerable effort has been directed toward development of a model to predict the magnitude of DDIs using in vitro data.…”
Section: Discussionmentioning
confidence: 99%
“…7B). JBP485 is a dipeptide (Liu et al, 2000) with antihepatitis and gastrointestinal protective effects (Liu et al, 1998;Wu et al, 2008) that was first isolated from Laennec (Yang et al, 2009), a substrate of OAT1 and OAT3 (Zhang et al, 2010). We found that PCG, probenecid, JBP485, and aspirin inhibited the uptake of cilostazol in a concentration-dependent manner (Fig.…”
Section: Mechanism Of Ddi Between Cilostazol and Aspirin Or Probenecimentioning
confidence: 72%